Investment Sensitivity Analysis of Transjatim Corridor I Luxury Sidoarjo-Surabaya-Gresik Route - Novalia, Kiki Devita; Muhammadun, Haris; Marleno, Risma (International Journal of Social Science and Community Service, 2024)
Based on the recapitulation of Transjatim Corridor I passengers in 2023, the average load factor is 120%, with an average of 5-6 thousand passengers per day, leading to the addition of a fleet with luxury services. This study aims to analyze the financial feasibility of investment in the Transjatim Luxury Bus Corridor I by comparing income and expenditure variables using the Net Present Value (NPV), Benefit-Cost Ratio (BCR), Internal Rate of Return (IRR), and Payback Period (PP) methods. With a 6% discount rate, the analysis yielded NPV values > 0 (Rp. 5,204,972,631 for alternative 1, Rp. 2,466,479,592 for alternative 2, and Rp. 640,817,566 for alternative 3), IRR values > 6% (19.42% for alternative 1, 12.54% for alternative 2, and 7.74% for alternative 3), and BCR values > 1 (1.30 for alternative 1, 1.19 for alternative 2, and 1.11 for alternative 3). The PP values were 4 years for alternative 1, 5 years for alternative 2, and 6 years for alternative 3, indicating that all three alternatives are financially feasible. Sensitivity analysis confirmed the financial feasibility of all three alternatives, considering the effect of the discount rate on NPV.